2014
DOI: 10.1155/2014/801590
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of Temperature Ranges between the Top and Bottom of an Air Flow Controlling Device through Hybrid Control in a Plant Factory

Abstract: To maintain the production timing, productivity, and product quality of plant factories, it is necessary to keep the growth environment uniform. A vertical multistage type of plant factory involves different levels of growing trays, which results in the problem of difference in temperature among vertically different locations. To address it, it is necessary to install air flow devices such as air flow fan and cooling/heating device at the proper locations in order to facilitate air circulation in the facility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Zhu et al [160] used the remote wireless system for water quality online monitoring in intensive aquaculture using artificial neural networks. The results demonstrate that online monitoring for water quality information could be 12 Journal of Sensors accurately acquired and predicted by using the remote wireless system. Mahajan et al [161] reported that agriculture is noteworthy that computer vision applications have grown due to reduced equipment costs, increased computational power, and increasing interest in nondestructive food assessment methods.…”
Section: Application Of Artificial Intelligence Techniques In Agriculmentioning
confidence: 80%
See 1 more Smart Citation
“…Zhu et al [160] used the remote wireless system for water quality online monitoring in intensive aquaculture using artificial neural networks. The results demonstrate that online monitoring for water quality information could be 12 Journal of Sensors accurately acquired and predicted by using the remote wireless system. Mahajan et al [161] reported that agriculture is noteworthy that computer vision applications have grown due to reduced equipment costs, increased computational power, and increasing interest in nondestructive food assessment methods.…”
Section: Application Of Artificial Intelligence Techniques In Agriculmentioning
confidence: 80%
“…The method can provide sufficient food supply throughout the year. In the system, the plant grows around the year by artificially adjusting and controlling the surrounding environmental conditions such as temperature, CO 2 (carbon dioxide), humidity, light intensity, airflow, and nutrients supply within the confined facilities [11,12]. Besides, the system minimises environmental impact and maximises the crop yield with significant results as compared with traditional (open-field) cultivation system [13].…”
Section: Introductionmentioning
confidence: 99%
“…The main focus of research targets the development of more efficient and suitable LED lights for indoor horticulture, use of smart monitoring systems that optimize the operation of climate control equipment, automations for reductions in labor costs and more precise cultivation protocols for increased yield and quality. Finally, significant research exploits the usage of RES to limit the operating costs and reduce the environmental footprint of the farms [5,87,88,[121][122][123][124].…”
Section: Vertical Farmsmentioning
confidence: 99%
“…The method can provide sufficient food supply throughout the year. In the system, the plant grows around the year by artificially adjusting and controlling the surrounding environmental conditions such as temperature, carbon dioxide (CO2), humidity, light intensity, airflow, and nutrients supply within the confined facilities ( Moon et al, 2014;Lee & Yoe, 2015) . Besides, the system minimised environmental impact and maximised the crop yield with significant results as compared with traditional (openfield) cultivation system (Stanghellini, 2014).…”
Section: Introductionmentioning
confidence: 99%